SINANTHROPIZATION OF TRIATOMINES (HEMIPTERA: REDUVIIDAE) IN THE ITUMBIARA MUNICIPALITY, GOIÁS, BRAZIL - Alves de Camargo, Fernanda; Aline Romano, Camila; Natalina Elias, Carmeci; Helena Garcia da Silva, Heloisa; Garcia da Silva, Ionizete (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
This notification presents the occurrence of triatomines captured in the synanthropic environment in the urban area of the municipality of Itumbiara, Goiás. The colonies were found inside homes and on beds, walls, ceilings and counters. They were also found outside the houses on fences, in hen houses, pigeon nests and pigpens. In descending order, the infestation by triatomine species was: Triatoma sordida (99.7%), Rhodnius neglectus (0.2%) and Panstrongylus diasi (0.1%). Only the species T. sordida was infected by Trypanosoma cruzi, with an index of 5.5%.